Mobile and Web recommendation application in the Semantic Web paradigm. A case study - Łazaruk, Szymon; Dzikowski, Jakub; Kaczmarek, Monika; Abramowicz, Witold (Internecie semantycznym. Studium przypadku, 2012)
This paper focuses on a Mobile and Web-based Recommendation application operating on the Semantic Web’s resources, called Taste It! Try It!. The application consumes Linked Data (while creating the reviews), producing semantic annotations (about the reviewed entities), and then querying the gathered data using the reasoner in order to offer personalized recommendations. Within this paper, we present the final prototype of the tool and its functionalities
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 3 (25), s. 109-122
Keywords: Recommendation System; semantic annotations; incentive mechanisms; systemy rekomendujące; semantyczne adnotacje; mechanizmy motywujące